Cientific school of academician Maxym Martynovych Palamarchuk (dedicated to the scientist’s 100th birthday anniversary) - Serhiy Shevchuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2017)
The article reveals features of a complex comprehensive study of the formation and the development of a large personal scientific school o fAcad. M. Palamarchuk(1916 – 2000) according to its size and significant research results in the theory and practice of national social geography. The basic stages of scientific results of Acad. M. Palamarchuk as the founder and the leader of the scientific school of geographical bases of improvement of territorial organization of a society and complex maintaining in the economy were defined in the article. On account of personal analysis of the scientific school of Acad. M. Palamarchuk his contribution to the development of social and geographical sciences, the author of the article gave the names of doctors of science trained by M. Palamarchuk (M. Pistun, Ya. Zhupanskyi, I. Gorlenko, L. Rudenko, R. Yazynina, R. Ivanuh, S. Pysarenko, D. Stechenko, G. Balabanov, P. Maslyak, M. Faschevskyyб V. Nagirna, V. Semenov, S. Ishchuk, Ya. Oliinyk) and the names of PhD scholars (R. Yazynina, S. Ishchuk, I. Gorlenko, V. Zhabytska, M. Kuryliuk, R. Lytvynenko, N. Protsko, K. Tashchuk, V. Belozorova, M. Faschevskyi, D. Stechenko, T. Yasnyuk, E. Bitayeva, G. Balabanov, I. Pushkar, S. Maliuk, L. Nemchenko, V. Semenov, I. Smyrnov, P. Maslyak, Ya. Oliynyk, V. Polyukhovych, A. Tkachov, A. Zastavetska, O. Krayovyi, A. Kuz'myns'ka, K. Pyrozhenko, L. Kovtun, V. Zakharchenko, V. Schabelska, M. Bredyhin, S. Lisowskyi, Y. Palekha). Also the scientific schools established by the followers of Acad. M. Palamarchuk, primarily by doctors of science, were figured out.